2017
DOI: 10.1159/000479154
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Capecitabine, Oxaliplatin, and Irinotecan in Resectable Gastric or Gastroesophageal Junction Cancer: Pathological Response as Primary Endpoint and FDG-PET Predictions

Abstract: Objectives: This phase II trial was aimed at assessing the safety and activity of capecitabine, oxaliplatin, and irinotecan (COI regimen) as a preoperative treatment for resectable gastric cancer (GC) or gastroesophageal junction (GEJ) cancer. Methods: Patients affected by T3-T4/N0-N+/M0 GC/GEJ cancer were treated with the COI regimen for 4 cycles followed by restaging and gastroresection with D2 lymphadenectomy. Four postoperative cycles were scheduled. The primary endpoint was pathological response rate acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Other studies evaluating neoadjuvant chemotherapy for GC also demonstrated comparable gastrectomy and disease progression rates [ 20 , 21 ]. The MPR rate in neoadjuvant nivolumab monotherapy (16%) was also comparable with those (6%–32%) in patients with GC receiving neoadjuvant chemotherapy [ 4 , 20 22 ]. However, such comparisons should be interpreted with caution, given that patients enrolled in the current study had GC at relatively early clinical stages.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Other studies evaluating neoadjuvant chemotherapy for GC also demonstrated comparable gastrectomy and disease progression rates [ 20 , 21 ]. The MPR rate in neoadjuvant nivolumab monotherapy (16%) was also comparable with those (6%–32%) in patients with GC receiving neoadjuvant chemotherapy [ 4 , 20 22 ]. However, such comparisons should be interpreted with caution, given that patients enrolled in the current study had GC at relatively early clinical stages.…”
Section: Discussionmentioning
confidence: 78%
“…In the FLOT4 study, the representative neoadjuvant chemotherapy achieved a 94% gastrectomy rate; however, 2% of patients suffered from disease progression or died during the neoadjuvant chemotherapy [3]. Other studies evaluating neoadjuvant chemotherapy for GC also demonstrated comparable gastrectomy and disease progression rates [20,21]. The MPR rate in neoadjuvant nivolumab monotherapy (16%) was also comparable with those (6%-32%) in patients with GC receiving neoadjuvant chemotherapy [4,[20][21][22].…”
Section: Considering Relatively High Rate Of Disease Progressionmentioning
confidence: 89%
See 1 more Smart Citation
“…Irinotecan is a DNA topoisomerase I inhibitor, which can treat tumors by inhibiting the mitosis of tumor cells and is suitable for advanced cancer chemotherapy [6][7][8][9]. As previously noted, CEA positivity was associated with lymph node involvement; the decrease of CA72-4 after neoadjuvant chemotherapy could predict pathologic response; elevated CA19-9 levels appeared to be of disease control after neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 73%
“…The use of PET CT in gastric cancer in assessing the response to preoperative therapies is under investigation. A study from Italy published in 2017 showed that in patients with resectable T3-T4 and/or N+, M0 gastric or EGJ adenocarcinoma undergoing perioperative chemotherapy with irinotecan-oxaliplatin-capecitabine, pathologic response correlated with the baseline SUV level of the primary tumor and not with the SUV change following treatment [41]. In another study from Germany published in 2010, the authors did not identify a statistically significant association between pre-and post-treatment SUV levels and histologic response or prognosis in patients with LAGC undergoing neoadjuvant treatment with cisplatin-leucovorin-5FU (PLF) [42].…”
Section: Radiographic and Endoscopic Response To Chemotherapy And Pro...mentioning
confidence: 99%